2020
DOI: 10.26452/ijrps.v11i4.3172
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome And Mortality Assessment Following Proximal Femoral Nailing In Inter Trochanteric Fracture

Abstract: Intertrochanteric fractures constitute one of the most typical fractures of the hip. The incidence of fractures in the trochanteric area has risen with an increase in numbers of the older person with osteoporosis. Mortality, morbidity ratios are increasing in patients with inter-trochanteric fractures. Advanced age and associated co-morbidities are two primary added source for high mortality in trochanteric fracture patients. We conducted this study to assess the mortality rate and the functional outcome in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…In our study the most common mode of injury was simple fall (62.5%) where as in Huang et al study has observed both RTA and simple fall as the commonest mode of injury 6 and in the study done by Prabhakaran et al showed 76.7% patients had simple fall compared to RTA (23.3%) 2 . 66.7% had right side injury in our study.…”
Section: Vas Scoringsupporting
confidence: 69%
See 3 more Smart Citations
“…In our study the most common mode of injury was simple fall (62.5%) where as in Huang et al study has observed both RTA and simple fall as the commonest mode of injury 6 and in the study done by Prabhakaran et al showed 76.7% patients had simple fall compared to RTA (23.3%) 2 . 66.7% had right side injury in our study.…”
Section: Vas Scoringsupporting
confidence: 69%
“…In the study done by Prabhakaran et al majority had left side injury 55% 2 . In our study we have used AO classification to classify intertrochanteric fractures and it was found that most common type was 31A2.2 (37.5%), Aspenberg et al reported 50% of the population having 31A1 (50%) type of fracture 11 , whereas Kim et al has reported 87.5 % of fracture type 31A2 14 .…”
Section: Vas Scoringmentioning
confidence: 91%
See 2 more Smart Citations